Implementation of Teachers’ Registration Council of Nigeria Guidelines in Kwara State, Nigeria - Imam-Tamim, M. K.; Fasasi, Y. A.; Ottan, Jamiu Olatunji (International Journal of Educational Management, 2021)
The purpose of this study was to investigate implementation of Teachers’ Registration Council of Nigeria guidelines in secondary schools in Kwara state, Nigeria. Cross-sectional survey design was adopted for the study. 370 teachers and 66 staff of TRCN out of the 9, 803 teachers and 79 TRCN staff respectively were selected as research participants. A researcher-designed questionnaire labelled: “Implementation of Teachers’ Registration Council of Nigeria Guidelines Questionnaire” (ITRCNGQ) was used to obtain data for the study. The questionnaire was administered to the respondents using electronic social media platforms. Both descriptive and inferential statistics were used to analyse the data collected. The findings of the study showed among others: that the level of awareness of the TRCN guidelines is not good enough as majority of the respondents only have good level of awareness about accreditation but low level of awareness about monitoring, internship and annual examination; and that the level of implementation of the TRCN guidelines was rated fair showing that much still needs to be done by the body. Based on the findings of the study, it was recommended, among others, that the TRCN should improve its level of implementation of other guidelines in the Professional Standards for Nigerian Teachers (PSNT) other than the accreditation aspect only. Also, the Federal Government should improve upon the resources and facilities available to TRCN in order that their monitoring would traverse the nooks and crannies of the state to cover both the urban and rural school locations.